2010
DOI: 10.2131/jts.35.619
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the embryonic stem cell test endpoint analysis by use of field potential detection

Abstract: -The embryonic stem cell test (EST) is a validated in vitro method to assess the embryotoxic potential of compounds and is a promising tool for drug screening. EST requires microscopic observation of beating cardiomyocytes differentiated from embryonic stem cells as a toxicological endpoint. However, this process is time-consuming and lacks throughput performance. To improve the analysis, we introduced an electrophysiological method with a microelectrode array system for the evaluation of differentiated cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The changes of these parameters in 5-FU treated EBs were almost same as in previous papers Seiler et al, 2004;Koseki et al, 2010). Furthermore, the study also confirmed the relationship between expression area of cTnT and field potential signal or beating in these in 5-FU treatment groups, and concordance rate of these parameters was more than 70%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The changes of these parameters in 5-FU treated EBs were almost same as in previous papers Seiler et al, 2004;Koseki et al, 2010). Furthermore, the study also confirmed the relationship between expression area of cTnT and field potential signal or beating in these in 5-FU treatment groups, and concordance rate of these parameters was more than 70%.…”
Section: Discussionsupporting
confidence: 88%
“…EST, however, requires microscopic observation of beating cells to be considered cardiomyocytes differentiated from ES cells as an endpoint assay; this process is time-con- suming and a restricting factor for throughput performance, and some alternative methods to this endpoint assay have been developed (Bremer et al, 2001;Buesen et al, 2009;Peters et al, 2008;Seiler et al, 2004). In a previous study, we established a novel method to evaluate the differentiation of ES cells based on a field potential formulation for cardiomyocytes (Koseki et al, 2010). This field potential method can be performed automatically and can improve the throughput performance compared to the original EST method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These study systems, however, are not appropriate for early-stage drug screening because they are low-throughput and time-consuming. Therefore, some alternative in vitro methods, e.g., embryonic stem cell test (EST: (Scholz et al, 1999)), mammalian micromass (MM) test (Flint, 1993), and whole embryo culture (WEC) test (Webster et al, 1997) have been validated by the European Centre for the Validation of Alternamethods have been reported (Peters et al, 2008;Koseki et al, 2010;Suzuki et al, 2011) to achieve more efficient throughput ability. Although these in vitro methods are useful for prediction of embryotoxicity or teratogenicity, drug exposure timing of MM or WEC test does not cover the whole period of organogenesis, and EST methods do not consider the complexity of embryotoxic mechanisms other than cardiac development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alternatives to animal testing have been actively sought from the viewpoint of the 3Rs principle for a more ethical use of animals in testing. To date, whole embryo culture (WEC) 17 and embryonic stem cell test (EST) 18 have been established as in vitro assay systems with modest throughput. However, these assay systems are not commonly used in drug discovery, because the culture period (of up to 3 days) prevents the use of WEC for evaluating the entire organogenesis process and EST has only been used to evaluate differentiation into cardiomyocytes.…”
Section: Examples Of Applicationsmentioning
confidence: 99%